Evaluation of the Efficiency of Alveolar Opening in Cardiosurgical Patients with Low Left Ventricular Ejection Fraction - Yu. G Zorina; V. V. Moroz; A. M Golubev; Yu. V. Nikiforov (Общая реаниматология, 2009)
Objective: to determine the optimum alveolar opening parameters for the improvement of postoperative pulmonary oxygenizing function in patients with a left ventricular ejection fraction (LVEF) of less or more than 40% after aortocoronary bypass surgery (ACBS). Subjects and methods. Twenty patients with a LVEF of less than 40% after ACBS and with postoperative pulmonary oxygenizing dysfunction (PaO2/FiO2 less than 250) (Group 1) were examined. A control group consisted of 20 patients with a LVEF of more than 40% (Group 2). Gas exchange, respiration biomechanics, and central hemodynamic (CH) parameters were monitored (a Vigilance monitor (Edvard LifeScience)). Alveolar mobilization was carried out on Drager Evita-2 apparatuses in the BIPAP mode, by taking into account the previous artificial ventilation (AV) parameters. The low pressure phase corresponded to the positive end-expiratory pressure (PEEP) with volume AV, the high pressure phase was Pplato; the duration of both phases — that of inspiration and expiration (the high pressure phase was inspiration time; the low pressure phase was expiration time). Then the values of Pplato and PEEP were simultaneously increased by 2 cm H2O with a duration of 10 breathing cycles, by continuously monitoring Vt and SaO2 over this interval. By continuously monitoring Vt, a stepwise increase in PEEP and Pplato was continued until there was a Vt reduction or a negative impact of AV on CH. All alveoli were considered to be open when the maximum Vt and SaO2 were achieved. Conclusion. In Group 1 patients with Pinsp of 27—30 cm H2O, PEEP of 10—12 cm H2O, there are increases in PaO2/FiO2 and Cst. In Group 2, the increase of PaO2/FiO2 and Cst is observed with Pinsp of 30—35 cm H2O and PEEP 12—14 cm H2O. With these AV indices, there is an allowable hemodynamic reduction that results in no negative consequences and development of cardiovascular events. After switching to AV in an individually chosen mode, all hemodynamic parameters return to the baseline level. Consequently, the proposed AV mode and ventilation parameters are safe and effective for the prevention of early postoperative respiratory failure in cardiosurgical patients. Key words: recruiting ventilation, positive end-expiratory pressure, alveolar opening.